ECONOMIC CRISIS AND THE COMPETITIVENESS OF TRANSNATIONAL COMPANIES - LIVIU RADU; CARMEN RADU (Challenges of the Knowledge Society, 2012)
In crisis situations, the competitiveness of transnational companies becomes a particularly complex concept, due to the fact that said business entities are continuously moving within the context of internationalization and increasing use of global strategies. Given the current economic context, one cannot merely assess the competitiveness level of any given transnational company from a static standpoint, depending on the turnover, sales volume or number of employees of said company, but such assessment needs to be made from a dynamic standpoint, in close connection with the internal and international business environment in which that company carries out its activity.